2021
DOI: 10.1186/s12888-021-03270-7
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to retinal nerve fiber layer thickness in bipolar disorder patients and major depression patients

Abstract: Background We analyzed the correlation of the clinical data with retinal nerve fiber layer (RNFL) thickness and macular thickness in bipolar disorder patients and major depression patients. The aim of this study is to explore factors that affect RNFL thickness in bipolar disorder patients and major depression patients, with a view to providing a new diagnostic strategy. Methods Eighty-two bipolar disorder patients, 35 major depression patients and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…In the past, in individuals with MD, the retinal structure using the OCT test examination was investigated in 5 case-control studies with mixed results. 14,[38][39][40][41][42] Jung et al described decrease of ganglion cell inner plexiform layer thickness in individuals with MD. 12 Kalenderoglu et al showed significantly reduced GCL, IPL, and global and temporal superior retinal nerve fiber layer (RNFL) thickness in the recurrent-MD individuals compared to the first-episode individuals, and in all MD individuals compared with the controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past, in individuals with MD, the retinal structure using the OCT test examination was investigated in 5 case-control studies with mixed results. 14,[38][39][40][41][42] Jung et al described decrease of ganglion cell inner plexiform layer thickness in individuals with MD. 12 Kalenderoglu et al showed significantly reduced GCL, IPL, and global and temporal superior retinal nerve fiber layer (RNFL) thickness in the recurrent-MD individuals compared to the first-episode individuals, and in all MD individuals compared with the controls.…”
Section: Discussionmentioning
confidence: 99%
“…42 However, other researchers, like in our study comparing the MD individuals with the healthy controls, found no statistically significant differences in the OCT measures. [39][40][41] The feature of abnormal ISCEV-standard PVEPs response has clinical relevance. The PVEPs signal might serve as an objective marker of the major depression and has a potential value in monitoring pharmacological and nonpharmacological treatment trials.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have employed OCT to reveal that patients with bipolar disorder have thinner RNFL compared with healthy controls,26 which has also been linked to disease duration 27. Age at onset and alanine aminotransferase (ALT) could be potential protective factors in the progress of RNFL thinning, whereas uric acid is a pathological factor in patients with bipolar disorder 28. Studies have also adopted OCT to reveal marked RNFL and macula lutea thinning in patients with MDD relative to normal people 28.…”
Section: Discussionmentioning
confidence: 99%
“…As a neurodegenerative disease, the diagnosis of MDD mainly relies on the patient’s subjective assessment and lacks quantifiable objective indicators. Although previous studies have demonstrated the structural alterations of the retina in MDD patients, such as thinner RNFLT ( 36 ), reduced minimum ganglion cell-inner plexiform layer and poor visual function ( 37 ), a highly reliable retinal-related indicators for screening of early-stage MDD remains to be identified for the following reasons. First, previous research indicators on the retina of MDD patients are relatively single, mostly focusing on retinal thickness, and a comprehensive and systematic analysis of the retina is lacking.…”
Section: Discussionmentioning
confidence: 99%